2017
DOI: 10.1186/s13102-017-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

The FIFA 11+ injury prevention program for soccer players: a systematic review

Abstract: BackgroundSoccer is one of the most widely played sports in the world. However, soccer players have an increased risk of lower limb injury. These injuries may be caused by both modifiable and non-modifiable factors, justifying the adoption of an injury prevention program such as the Fédération Internationale de Football Association (FIFA) 11+. The purpose of this study was to evaluate the efficacy of the FIFA 11+ injury prevention program for soccer players.MethodologyThis meta-analysis was based on the PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(123 citation statements)
references
References 43 publications
2
93
0
10
Order By: Relevance
“…A meta‐analysis by Neto et al published in 2016 included 11 primary studies. The two meta‐analyses published in 2017 each included only six studies . Only three out of fifteen primary studies were cited in all four meta‐analyses: Soligard et al, Steffen et al, and Owoeye et al The overlap between included primary studies was very high, yielding a CCA score of 37.7%.…”
Section: Resultsmentioning
confidence: 99%
“…A meta‐analysis by Neto et al published in 2016 included 11 primary studies. The two meta‐analyses published in 2017 each included only six studies . Only three out of fifteen primary studies were cited in all four meta‐analyses: Soligard et al, Steffen et al, and Owoeye et al The overlap between included primary studies was very high, yielding a CCA score of 37.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, simple main effect of time revealed that both groups improved performance in the Sit and Reach test, the FIFA 11+ (F (1,18) = 23.81, p < 0.001, ŋ 2 p = 0.569) and CG (F (1,15) = 7.21, p = 0.017, ŋ 2 p = 0.325). Although the established level of significance (p ≤ 0.05) was not achieved for the interaction effect on VO 2 max, simple main effect of time showed that the mean VO 2 max significantly improved from pre-to post-test in the FIFA 11+ (F (1,18 ) = 22.22, p < 0.001, ŋ 2 p = 0.529), but not in the CG (F (1,15) = 2.85, p = 0.112, ŋ 2 p = 0.160). The changes from pre-to post-test in the remaining studied physical performance outcomes for FIFA 11+ and CG were not significant ( Table 2).…”
Section: Rsa Tt (S)mentioning
confidence: 92%
“…18.63 ± 0.93 18.27 ± 0.93 * Group: F (1, 103) = 3.68, p = 0.126, ŋ 2 p = 0.07 Time: F (1, 103) = 6.9, p = 0.013, ŋ 2 p = 0.173 Group × Time: F (1,103) =7.91, p = 0.008, ŋ 2 p = 0.193 F (1, 103) = 7.91, p = 0.008, ŋ 2 p = 0.193 CG 18.04 ± 1.21 18.05 ± 1.19…”
Section: Fifa 11+mentioning
confidence: 99%
See 2 more Smart Citations